The mutational landscape of ARMC5 in Primary Bilateral Macronodular Adrenal Hyperplasia: an update - Lucas Bouys; Anna Vaczlavik; Isadora P. Cavalcante; Florian Violon; Anne Jouinot; Annabel Berthon; Patricia Vaduva; Stéphanie Espiard; Karine Perlemoine; Peter Kamenicky; Marie-Christine Vantyghem; Antoine Tabarin; et al. (Orphanet Journal of Rare Diseases)
Abstract Background Primary Bilateral Macronodular Adrenal Hyperplasia (PBMAH) is a rare cause of Cushing’s syndrome due to bilateral adrenocortical macronodules. Germline inactivating variants of the tumor suppressor gene ARMC5 are responsible for 20–25% of apparently sporadic PBMAH cases and 80% of familial presentations. ARMC5 screening is now routinely performed for PBMAH patients and families. Based on literature review and own observation, this study aims to give an overview of both published and unpublished ARMC5 genetic alterations and to compile the available evidence to discriminate pathogenic from benign variants. Results 146 different germline variants (110 previously published and 36 novel) are identified, including 46% missense substitutions, 45% truncating variants, 3% affecting splice sites, 4% in-frame variants and 2% large deletions. In addition to the germline events, somatic 16p loss-of-heterozygosity and 104 different somatic events are described. The pathogenicity of ARMC5 variants is established on the basis of their frequency in the general population, in silico predictions, familial segregation and tumor DNA sequencing. Conclusions This is the first extensive review of ARMC5 pathogenic variants. It shows that they are spread on the whole coding sequence. This is a valuable resource for genetic investigations of PBMAH and will help the interpretation of new missense substitutions that are continuously identified.